Lear and the learned Theban - David Ian Clive Lucking (Lingue e Linguaggi, 2014)
Abstract - The affinities between Shakespeare’s King Lear and Sophocles’ Oedipus the King, and in particular the pattern of allusion to eyes and to eyesight developed in both plays, is familiar critical terrain. The purpose of this essay is to consider in a somewhat broader perspective King Lear’s relation not only with Oedipus the King, but with the entire group of works generally referred to as the Theban plays. Elements in common between the works by Shakespeare and Sophocles, among which are the eyesight motif and its symbolic connotations, the figures of devoted daughters, a concern with relationships between parents and children, and an interest in what constitutes real knowledge of the self and of the world, are discussed in the first section of the essay. The question of why such parallels should exist, and in particular of whether Shakespeare knew Sophocles’ works either at first hand or as mediated through the derivative plays of Seneca, is investigated in the second part, while in the third the symbolic implications of the sight pattern shared by the works are examined in depth. Keywords: Shakespeare, Sophocles, King Lear, Theban plays, Oedipus.